Megabenthos and benthopelagic fishes on Southeast Atlantic seamounts. Issue 1 (2nd January 2019) - Bergstad, OA; Gil, M; Høines, ÅS; Sarralde, R; Maletzky, E; Mostarda, E; Singh, L; António, MA; Ramil, F; Clerkin, P; Campanis, G
Abstract : In a descriptive study of megafauna of several Southeast Atlantic seamounts, multiple video-transects on upper slopes and summits documented the occurrence of benthic invertebrate taxa, primarily corals, regarded as indicators of vulnerable marine ecosystems (VMEs) as defined in international guidelines. At Schmitt-Ott Seamount there was a pronounced dominance of gorgonian corals (seafans, Alcyonacea). In all other study areas the diversity was greater, and more scleractinians (stony corals, Scleractinia) were observed. Scleractinian corals were mainly dead, and much of the coral framework and rubble may have been ancient. In the Valdivia complex and on Ewing Seamount, which are open to fisheries, scleractinians seemed restricted to some slopes of knolls, and on Valdivia Bank and the subarea denoted Valdivia West the summit substrate was mostly bare rock. Pelagic armourhead Pseudopentaceros richardsoni and splendid alfonsino Beryx splendens (two targets of commercial fisheries in the area) were observed at a few sites, but did not appear to be abundant in the main former fishing areas of the Valdivia area. Orange roughy Hoplostethus atlanticus was common in video records around the summit at Ewing Seamount. The deep-sea red crab Chaceon erytheiae was abundant in the Valdivia area and at Ewing Seamount, and crabs were distributed across a more extensive depth range than the fishes. In areas with high densities of live coral, the video records suggested that the benthic communities were intact and not impacted by fishing. Evidence of past fishing activities included observations of lost pots and rope at Vema Seamount and in the Valdivia area.